Pelaksanaan Fungsi Dinas Penanaman Modal dan PelayananTerpadu Satu Pintu Kota Kupang Dalam Penyelenggaraan Persetujuan Bangunan Gedung Di Kota Kupang Di Tinjau Dari Peraturan Walikota Nomor 50 Tahun 2021 Tentang Kedudukan, Susunan Organisasi, Tugas Dan Fu - Djami, Rally Sunardo; Monteiro, Yosef Mario; Yohanes, Saryono (Artemis Law Journal, 2024)
Licensing plays a crucial role in regulating societal activities, aiming to foster order, fairness, and prosperity. Despite its significance, challenges persist within the Investment and Integrated One-Stop Service Office (DPMPTSP), particularly in Kupang City, where residents face hurdles in adapting to digitalization. This lack of understanding exacerbates issues such as low awareness of Building Construction Approval (PBG), leading to a disconnect between the community and the government. This thesis addresses: (1) The effectiveness of DPMPTSP in facilitating PBG in Kupang City; and (2) Factors hindering its implementation. Conducted as an empirical legal study at DPMPTSP, it involved primary and secondary data analysis. Findings reveal: (a) Monitoring is hindered by server maintenance and public unfamiliarity with PBG procedures. (b) Despite regulatory efforts, PBG processes have evolved with the introduction of a web-based system called the Building Management Information System (SIMBG). (c) Recommendations from DPMPTSP remain partially implemented, reflecting a gap in public-government understanding. Recommendations include staffing, infrastructure upgrades, and public education to bridge this divide.